Limitations on Primary Frequency Control Adequacy Constraints in the Economic Dispatch - Chavez-Orostica, H; Acosta-Barbosa, K (Institute of Electrical and Electronics Engineers Inc., 2019)
The integration of renewable energy has reduced the ability of power systems to maintain primary control adequacy, leading to formulations that represent such an adequacy in the economy dispatch. It can be seen that the various approaches rely on sufficient condition to guarantee adequacy, while sufficient and necessary condition are not yet proposed. It is not then clear if the sufficient conditions are far from being necessary, or if they represent a significant impact on the economic decision. This work explores different conditions to understand the impacts sufficient but not necessary condition of Frequency Control Adequacy Constraints on the Economic dispatch, by simulating both the dynamics of frequency control and the optimization problem behind economic dispatch. An illustrative case is presented. © 2019 IEEE.